Implementasi Metode Wetonan pada Pembelajaran Kitab Kuning di Pondok Pesantren Mu’allimin Muhammadiyah Pakan Sinayan Kamang Mudik Agam - Uminisara, Uminisara; Satria, Rengga (Lembaga Yasin AlSys, 2024)
The yellow book is an important factor that is characteristic of the Pondok Pesantren. The Yellow Book is functioned by the peasantren as a reference whose content is no longer needed to be questioned, of such that the problem is that the chancellor in the Podok Pasantren Mu’allimin Muhammadiyah Pakan Sinayan Kamang Mudik Agam has a low interest in following the lessons of the yellow books before applying the method of wetonan. This research aims to find out how the implementation of the wetonan method in learning the yellow book so that the centurion puts an interest in following him at every meeting. This research uses qualitative methods with the type of field research. The sample was the head of the school, the yellow book teacher, and the chancellor of the Pondok Pesantren Mu’allimin Pakan Sinayan. Data collection techniques using interviews, observations and documentation. Data analysis techniques using descriptive qualitative. Data validation techniques using source tringulation and tringulation techniques. The results of this study show that the wetonan method is more effective in yellow book learning, characterized by the absence of a centri who has no alpha description (without description) within a week. The steps of implementation of the method of wetonan in Pondok Pesantren Mu’allimin Pakan Sinayan Kamang Mudik Agam are: 1) Teacher reads Arabic sentences and dictates their sentences 2) Teacher translates 3) Teacher notes the meaning of words and important things 4) Teacher explains the significance of sentences. eval__uation of yellow book learning by means of mid-term and end-term exams. The factor of this learning is first, the book has been available in the library. Secondly, teachers who are good at teaching. The first factor is the short duration of the study, and the second is that the teacher is not a graduate of the training program.